Effect of submergence durations on yield and yield contributing characters of hybrid and inbred aman rice (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
The trend of increasing submergence has a negative effect on the rice yield but among them, some of the genotypes show the excellent performance to give a satisfactory yield. The experiment comprised of two factors-factor a: submergence duration (4): control, 6 days, 10 days and 14 days and factor b: rice variety (6): hybrid (BRRI Hybrid dhan3, ACI Shankar and Heera-2) and inbred (BRRI dhan34, BRRI dhan46 and BRRI dhan51). The experiment was laid out in a randomized complete block design (RCBD) with three replications. Significant variation was found on different yield contributing characters and yield with submergence durations. In all the varieties, the control treatment (0 days submergence) showed the highest values (except the number of unfilled spikelets panicle-1) and was gradually decreased with increasing submergence duration from 6 days to 14 days. The lowest reduction due to submergence was recorded in BRRI dhan51, which was followed by BRRI dhan46. Attaining better yield, which was near about control, the varieties BRRI dhan51 and BRRI dhan46 proved them as relatively submergence tolerant compared to other varieties.Asian Australas. J. Biosci. Biotechnol. 2018, 3 (3), 225-230